2009
DOI: 10.1016/j.crme.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Full coverage film cooling using compound angle

Abstract: An experimental and numerical study is carried out on a cooling film issuing from a multiperforated wall of a simplified combustor. The objectives of this work are to achieve a better understanding of the dynamics of the film and to construct an experimental database on a simplified geometry in order to test numerical models. A parametric study of film cooling efficiency based on the direction of the cooling air injection is presented and shows that a swirling injection greatly enhances the cooling efficiency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Compound angle injection on convex surface showed high film cooling effectiveness at moderate and high blowing ratios. Michel et al [18] have carried out experimental and numerical study on a cooling film issuing from a multiperforated wall of a simplified combustor. They have shown that the film thickness and turbulence are greatly increased by compound angle holes.…”
Section: Gaseous Film Cooling Studiesmentioning
confidence: 99%
“…Compound angle injection on convex surface showed high film cooling effectiveness at moderate and high blowing ratios. Michel et al [18] have carried out experimental and numerical study on a cooling film issuing from a multiperforated wall of a simplified combustor. They have shown that the film thickness and turbulence are greatly increased by compound angle holes.…”
Section: Gaseous Film Cooling Studiesmentioning
confidence: 99%
“…Michel and colleagues conducted experimental and numerical studies using a simplified combustion chamber platform with porous wall film cooling. This enhanced the understanding of film dynamics and established an experimental database on simplified geometries to validate numerical models [16]. S.R.…”
Section: Introductionmentioning
confidence: 97%
“…Ekkad [18] and Lee [19] studied the cooling efficiencies of different coolants with different densities at large compound angles and found that coolants with lower densities have higher cooling efficiencies. Brice Michel [20] experimentally found that the cooling efficiency can greatly be enhanced by a swirling injection. They compared different injection models with the experimental results and found that the standard model has significant difficulty in predicting high-accuracy results, while the multi-perforation model has high accuracy.…”
Section: Introductionmentioning
confidence: 99%